The problem of the Old Testament : hermeneutical, schematic & theological approaches - Garrett, Duane A. (Downers Grove IVP Academic, 2020)
"Christians throughout church history have struggled with the Old Testament-defining it, interpreting it, and reconciling it with the New Testament. In this thorough, accessible work, Duane A. Garrett surveys three primary methods Christians have used to handle the Old Testament, offering a way forward that is faithful to the text and to the Christian faith"--
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc